Diagnosis and treatment of sepsis-induced cardiomyopathy using hemosorption therapy: a case report - S. V. Dil; V. V. Kirilin; N. M. Ivanov; V. V. Ryabov (Российский кардиологический журнал)
Introduction. Sepsis is a life-threatening organ failure caused by the body’s dysregulated response to infection. The prevalence of sepsis-induced cardiomyopathy (SICM) in patients with sepsis ranges from 10 to 70%, while there are no special sections on SICM in the known resuscitation manuals. There is also a lack of large clinical trials evaluating the effectiveness of SICM treatment.Case. A 59-year-old patient was urgently hospitalized in the intensive care unit with shock of unknown origin. Emergency coronary angiography revealed no coronary obstruction. Two hours after admission, asystole was recorded with effective cardiopulmonary resuscitation, mechanical ventilation, infusion of inotropic and vasopressor drugs. The patient was diagnosed with leukocytosis up to 19*109/l, procalcitonin >0,5 ng/ml. Subsequently, stage 2 acute kidney injury, pneumonia, acute respiratory distress syndrome, sepsis, SICM, combined shock (cardiogenic, septic) were diagnosed. Antibiotic and hemosorption therapy using a CytoSorb column were started. On the 6th day, there was a improvement of hemodynamic parameters, a decrease in the rate of vasopressor infusion, and normalization of the left ventricular ejection fraction. The condition has stabilized with further favorable changes.Discussion. Despite the wide prevalence and high mortality in SICM, this condition is not well described in the literature, and there are no clear diagnostic criteria and treatment algorithms. This case demonstrates the effective treatment of SICM at the stage when the prognosis of patients becomes extremely unfavorable, reaching 90% mortality.Conclusion. This case demonstrates the effective treatment of SICM as an element of multiple organ failure, in the outcome of sepsis, using efferent methods, when the prognosis becomes extremely unfavorable. Personalized approach and management of these patients is critical to improve disease outcomes.